Microplastics - an emerging silent menace to public health - Pang, Li-Yin; Sonagara, Shola; Oduwole, Oreoluwatomide; Gibbins, Christopher; Kang Nee, Ting (Life Sciences, Medicine and Biomedicine, 2021)
Over the past few decades, microplastics have become increasingly ubiquitous in the environment and now contaminate the bodies of many living organisms, including humans. Microplastics, as defined here, are plastics within the size range 0.1 μm and 5 mm and are a worrying form of pollution due to public health concerns. This mini-review aims to summarise the route of entry of microplastics into humans and explore the potential detrimental health effects of microplastics. Trophic transfer is an important pathway for microplastic to be transferred across different groups of organisms, with ingestion is regarded as one of the major routes of exposure for humans. Other pathways include inhalation and dermal contact. The health consequences of microplastics manifest because these materials can translocate into the circulatory system and accumulate in the lungs, liver, kidney, and even brain, regardless of the route of entry. Health effects include gastrointestinal disturbances such as inflammation and gut microbiota disruption, respiratory conditions, neurotoxicity and potential cancers. Overall, while it is apparent that microplastics are causing adverse effects on different biological groups and ecosystems, current research is largely focused on marine organisms and aquaculture. Therefore, more studies are needed to investigate specific effects in mammalian cells and tissues, with more long-term epidemiological studies needed on human population considered to be at high-risk due to socioeconomic or other circumstance. Knowledge of the toxicity and long-term health impacts of microplastics is currently limited and requires urgent attention.